Lipid Secretion by Parasitic Cells of Coccidioides Contributes to Disseminated Disease - Peláez-Jaramillo, Carlos Alberto; Jiménez-Alzate, Maria Del Pilar; Araque-Marin, Pedronel; Hung, Chiung-Yu; Castro-Lopez, Natalia; Cole, Garry T. (Frontiers in Cellular and Infection Microbiology, 2021)
Coccidioides is a soil-borne fungal pathogen and causative agent of a human respiratory disease (coccidioidomycosis) endemic to semi-desert regions of southwestern United States, Mexico, Central and South America. Aerosolized arthroconidia inhaled by the mammalian host first undergo conversion to large parasitic cells (spherules, 80–100 μm diameter) followed by endosporulation, a process by which the contents of spherules give rise to multiple endospores. The latter are released upon rupture of the maternal spherules and establish new foci of lung infection. A novel feature of spherule maturation prior to endosporulation is the secretion of a lipid-rich, membranous cell surface layer shed in vivo during growth of the parasitic cells and secretion into liquid culture medium during in vitro growth. Chemical analysis of the culture derived spherule outer wall (SOW) fraction showed that it is composed largely of phospholipids and is enriched with saturated fatty acids, including myristic, palmitic, elaidic, oleic, and stearic acid. NMR revealed the presence of monosaccharide- and disaccharide-linked acylglycerols and sphingolipids. The major sphingolipid components are sphingosine and ceramide. Primary neutrophils derived from healthy C57BL/6 and DBA/2 mice incubated with SOW lipids revealed a significant reduction in fungicidal activity against viable Coccidioides arthroconidia compared to incubation of neutrophils with arthroconidia alone. Host cell exposure to SOW lipids had no effect on neutrophil viability. Furthermore, C57BL/6 mice that were challenged subcutaneously with Coccidioides arthroconidia in the presence of the isolated SOW fraction developed disseminated disease, while control mice challenged with arthroconidia alone by the same route showed no dissemination of infection. We hypothesize that SOW lipids contribute to suppression of inflammatory response to Coccidioides infection. Studies are underway to characterize the immunosuppressive mechanism(s) of SOW lipids.